IS COMMON CAROTID INTIMA MEDIA THICKNESS AN INDEPENDENT PREDICTOR FOR CORONARY ARTERY DISEASE - Masoume Sadeghi; Hamidreza Roohafza; Masoud Poormoghadas; Aliakbar Tavasoli; Ramin Heidari (ARYA Atherosclerosis, 2010)
ABSTRACT Introduction: Non-invasive measurement of carotid intima media thickness (IMT) has been noted as a marker for atherosclerosis and can serve as a predictor of cardiovascular accidents. The present study investigates the relationship between carotid IMT and coronary artery disease (CAD). Method: This is a descriptive, analytical cross-sectional study of 300 individuals referring to Isfahan Cardiovascular Research Center (ICRC). After history taking, clinical examinations, and recording body weight and height, the subjects' lipid profile and fasting blood sugar (FBS) were evaluated. The subjects were divided into two groups according to CAD risk factors. The two groups were adjusted based on coronary disease risk factors. Maximum common carotid IMT was measured via B-mode ultrasonography in all subjects. Those with atherosclerotic plaques were excluded from the study. Collected data were statistically analyzed by SPSS10. Results: 65% of the subjects were male and 35% were female. They had a mean age of 50.72 years. 130 subjects (43%) were placed in the CAD group and 170 (56.7%) in the non-CAD group. There was no significant difference between the two groups in respect of risk factors such as age, total cholesterol, cigarette smoking, body mass index (BMI), hypertension, HDL-C, and LDL-C. Common carotid IMT was evaluated in the two groups. IMT that of the CAD group was found to be 0.8 millimeters more than that of the non-CAD group, which represents a statistically significant difference. Discussion: Different studies have shown varying relationships between carotid IMT and CAD. Based on the results of this study and in view of the safety and simplicity of ultrasonographic carotid IMT measurement, IMT can be used as a predictor of atherosclerosis in coronary arteries.   Keywords: Intima-media, Carotid, Coronary Artery Disease (CAD), Ultrasonography